Dynamics of goat population and production in Papua and West Papua Provinces: Correlation and regression analysis (2000-2023) - Wajo, Mohamad Jen; Koibur, Johan F.; Iyai, Deni A.; Pakage, Stepanus; Pattiselanno, Freddy; Palulungan, John Arnold (Fakultas Peternakan Universitas Papua, 2025)
This study investigates the trends in goat population and meat production in Papua and West Papua from 2000 to 2023, analyzing the relationship between population growth, production output, and key management factors. Using secondary data from official sources such as the Central Statistics Agency (BPS) and the Department of Animal Husbandry, the study employs descriptive analysis, Pearson correlation, and both linear and non-linear regression models. The results indicate a significant positive correlation between goat population and meat production, particularly in Papua, where a cubic regression model explained 61.9% of the variability in production. In contrast, West Papua showed a weaker relationship with more fluctuations in production trends. The study underscores the importance of sustainable management practices, including feed quality and health care, to optimize goat production. These findings provide insights into improving goat farming in these regions through targeted interventions and policy alignment with national agricultural strategies.